THE VERNACULAR ARCHITECTURE PRINCIPLES IN MAKING MOUNTAIN ROCK FOUNDATION IN KENDARI CITY - Muhammad Zakaria Umar; Arman Faslih (SINERGI, 2018)
Ordinary audiences who do not have formal education such as builders are called vernacular architects. In Kendari City, in general, public housing is built by a vernacular architect. The foundations made by vernacular architects do not use empty stones and sand dunes. The foundation is made partially in the hole and is made partially on the surface of the soil. This research is aimed to formulate the knowledge of vernacular architect on mountain rock foundation. This type of qualitative research with the descriptive approach used in this research. The resource is determined by the snowball method. Data collection was done by observation and in-depth discussion on three construction workers. Data were analyzed by the descriptive method. The research concludes that the vernacular architect in making the mountain rock foundation is rigid but also flexible, in order to respond to earthquake disaster. Rigid principles are found on mountain rock foundations, empty stone plates, nail terms on empty stones, chicken claw foundations, hierarchy on the floor, sloof and foundation relationships. Flexible principles are found in sand dunes, empty stones, anchor depth, and mortar for plaster.